Crystallisation, mechanical properties and rheological behaviour of PLA composites reinforced by surface modified microcrystalline cellulose. (20th April 2016) - Li, H.; Cao, Z.; Wu, D.; Tao, G.; Zhong, W.; Zhu, H.; Qiu, P.; Liu, C.
Abstract : Microcrystalline cellulose chemically modified by 3-isocyanatopropyl triethoxysilane (K-MCC) was incorporated as reinforcement into a polylactic acid (PLA) matrix to prepare PLA/K-MCC composites by melt blending. X-ray diffraction showed that PLA's crystalline structure was not affected by the added K-MCC, but its degree of crystallinity increased somewhat. Differential scanning calorimetry indicated that, when 5 wt-%K-MCC was added to PLA, the crystallisation of PLA improved greatly, and the degree of crystallinity reached a maximum of 39.4%, which exceeded that of pure PLA. Mechanical testing revealed that the tensile strength, modulus and heat distortion temperature of PLA also increased significantly after modified MCC was added, and the optimum mechanical properties of the composite were obtained. Dynamic rheological tests revealed shear thinning behaviour in the PLA/K-MCC composites. With increasing shear rate, more obvious shear thinning was observed because of more homogeneous dispersion of K-MCC with fewer hydroxyl groups in the PLA matrix.